Novel cationic peptide TP359 down-regulates the expression of outer membrane biogenesis genes in Pseudomonas aeruginosa: a potential TP359 anti-microbial mechanism. Issue 1 (December 2016) - Dosunmu, Ejovwoke F.; Chaudhari, Atul; Bawage, Swapnil; Bakeer, Mona; Owen, Donald R.; Singh, Shree; Dennis, Vida; Pillai, Shreekumar
Abstract Background Antimicrobial peptides (AMPs) are a class of antimicrobial agents with broad-spectrum activities. Several reports indicate that cationic AMPs bind to the negatively charged bacterial membrane causing membrane depolarization and damage. However, membrane depolarization and damage may be insufficient to elicit cell death, thereby suggesting that other mechanism(s) of action could be involved in this phenomenon. In this study, we investigated the antimicrobial activity of a novel antimicrobial peptide, TP359, against two strains ofPseudomonas aeruginosa, as well as its possible mechanisms of action. Results TP359 proved to be bactericidal againstP. aeruginosa as confirmed by the reduced bacteria counts, membrane damage and cytoplasmic membrane depolarization. In addition, it was non-toxic to mouse J774 macrophages and human lung A549 epithelial cells. Electron microscopy analysis showed TP359 bactericidal effects by structural changes of the bacteria from viable rod-shaped cells to those with cell membrane damages, proceeding into the efflux of cytoplasmic contents and emergence of ghost cells. Gene expression analysis on the effects of TP359 on outer membrane biogenesis genes underscored marked down-regulation, particularly ofoprF, which encodes a major structural and outer membrane porin (OprF) in both strains studied, indicating that the peptide may cause deregulation of outer membrane genes and reduced structural stability which could lead to cell death. Conclusion Our data shows that TP359 has potent antimicrobial activity againstP aeruginosa . The correlation between membrane damage, depolarization and reduced expression of outer membrane biogenesis genes, particularlyoprF may suggest the bactericidal mechanism of action of the TP359 peptide.